Barriers to treatment and care for depression among the youth in Uganda: The role of mental health literacy - Kennedy Amone-P'Olak; Adrian Ivan Kakinda; Henry Kibedi; Bernard Omech (Frontiers Media S.A., 2023)
BackgroundDepression represents a significant mental health problem (MHP) in low- and middle-income countries (LMICs), especially among early adults. Nevertheless, most early adults with depression do not seek treatment. Failure to recognize depression and knowledge about mental health literacy (MHL) may contribute to poor help-seeking behavior. This study assessed MHL, access and barriers to mental health care for depression among early adults in Uganda.MethodsData were collected from students in two of the largest universities in Uganda. Participants completed questionnaires on depression, MHL, sources of barriers and opportunities for MH service. Regression analyses and parametric tests were used to assess depression, access, barriers and opportunities to promote MH.ResultsAbout 12 per cent (n = 56) of the respondents were at the level of moderately severe to severe depression. Mental health literacy (MHL) scores were generally low ranging from "Ability to recognize mental disorders" (mean = 19.32, SD 3.22, range 18-32), and "Knowledge of risk factors" (mean = 4.39, SD 1.17, range 2-8), and "Knowledge of available information" (mean = 9.59, SD 2.53, range 5-20). Respondents reported barriers such as "stigma/discrimination" (65.53%), "lack of knowledge of where to receive help" (65.15%), "lack of trust in health workers" (62.56%), and "distant health facilities" (19.70%) that impede access to treatment and care. MHL significantly predicted depression (based on a continuous scale) (β = 0.63, 95% confidence interval [CI]: [0.56, 0.70]) with the regression model yielding a significant fit [R2 = 0.40, F (2, 460) = 189.84, p < 0.001].ConclusionsMHL is low among university students amidst several barriers such as stigma, fear, and lack of trust. To attenuate the negative effects of MHPs on wellbeing and lower the increased risk of psychopathology into adulthood, it is critical to prioritize MHL, address barriers to treatment and care, and develop the requisite infrastructure to tackle depression among early adults.